How US-China trade friction affects market opening in China: a comparative analysis between US-Japan and US-China trade friction - Kan, Pei Hsin (2020)
Since President Trump’s inauguration in 2017, rigorous US-China trade friction has rippled through global economy. Indeed, under President Trump’s America First doctrine, owing to China’s unfair trade practice, China has been the main target of US protectionist trade policy. Nevertheless, US-China trade friction is not the first case happening between the world’s two largest economies. In fact, the latest case of US-Japan trade friction of 1980s was not even far from us. Since the end of World War II, US has facilitated the global free trade system by opening domestic market to the world. However, the economic hegemony of US has therefore been seriously challenged afterward. Japan and China had been the representative challengers respectively in late 20th century and nowadays. By adopting export-oriented strategy and stateled industrial plan, both countries exploited the open market of US while closing domestic market from foreign competition, end up greatly undermining the trade profit of US. US thus inevitably adopted aggressive trade policy to rectify such unfair trade practice. This dissertation attempts to answer how US-China trade friction can affect market opening in China. By drawing lesson from historical US-Japan trade friction, this research identifies three favorable factors for US to virtually open Japan’s market in 1980s. However, through the comparative analysis with US-China trade friction, the favorable scenario is no longer found in current trade friction. Consequently, the conclusion is reached that by adopting similar aggressive trade policy, Trump administration can hardly open Chinese market to the comparable level that US once achieved in Japan, especially regarding to elimination of structural trade barriers.